(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
English immersion programme (EIP) or English as the medium of instruction (EMI) believes in the importance of maximum exposure to the target language. The use of English as the main language at school are both exciting but also challenging for the students since English is not widely used outside of the schools. Therefore, this study aims to investigate how the students perceive EIP or EMI as they go through formal education in Indonesia. This study was conducted as a case study of fifty-nine secondary students in an EIP school in Bandung, Indonesia. The data was collected through questionnaire and semi structured interviews. The data from questionnaire was analysed using descriptive statistics whereas thematic analysis was employed to analyze data from interviews. The findings show that the students have very positive attitude towards the EIP at school. The participants believe that by going to an EIP school, they developed their English skills much more rapidly compared to those who study in non-EIP schools. This study contributes to the discussions surrounding the practice of EIP or EMI in Indonesia and other countries where English is learned as a foreign language (EFL).